Implementasi Inovasi Pelayanan Malam “Mlebu Peteng” di Kantor Kecamatan Banjarsari Kota Surakarta - Widya Salma Khoirunnisa; Irsyadul Ibad (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Banjarsari Sub-district is one of the government agencies that has duties and functions in supporting public services, especially population administration services. To realize maximum service, Banjarsari Sub-district presents the “Mlebu Peteng” innovation, namely administrative services at night as a form of adaptation to the needs of people who have limited time during regular working hours. This innovation is an effort to improve service quality by expanding community access to public services. The purpose of this research is to describe the implementation of the “Mlebu Peteng” night service at the Surakarta City Banjarsari Sub-district Office and the obstacles experienced during the service process. The research method uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of the “Mlebu Peteng” innovation has helped the community in obtaining services outside working hours, with the level of community satisfaction reaching 91.77% in 2024. Based on George C. Edward III's policy implementation theory, the success of this innovation is supported by effective communication, adequate resources, positive disposition of officers, and a clear bureaucratic structure. However, there are several obstacles such as the lack of budget for officer incentives, uneven understanding of technology among staff, limited KTP-el recording services and SOPs that do not include mechanisms for handling technical complaints.